TEACHER TRAINING AND PEDAGOGICAL MEDIATION IN DISTANCE EDUCATION: CONTEMPORARY CHALLENGES IN LIGHT OF DECREE NO. 12,456/2025 - Pereira Barbosa, Célio (Revista Gênero e Interdisciplinaridade, 2026)
The expansion of Distance Education (DE) in Brazilian higher education has broadened the debate about the quality of pedagogical mediation and the training of professionals responsible for supporting students in virtual learning environments. In this context, Decree No. 12,456/2025 established new guidelines for this modality, formally recognizing the role of the pedagogical mediator and reinforcing the need for specific qualifications to perform this function. Given this scenario, this article aims to analyze the role of the mediating professor in DE, focusing on the challenges, competencies, and training gaps evidenced by the literature and a professional experience report. Methodologically, this is a qualitative, bibliographical, and descriptive-reflective research, articulated with an experience report developed in a private higher education institution. The results show that the role of the mediating professor demands cognitive, technological, and socio-affective competencies, as well as an understanding of the logic of poly-teaching and the need to support students with different levels of digital literacy. It is concluded that continuing education is a strategic element for the quality of pedagogical mediation, for student retention, and for the consolidation of educational practices aligned with the requirements of the new regulatory framework for distance education. The study contributes by advocating for the continuing education of mediating teachers as an institutional policy for academic quality and student retention.